Różne oblicza nacjonalizmów: polityka - religia - etos - Grott, Bogumił (Zakład Wydawn. "Nomos", 2010)
Zsfassung in engl. Sprache u.d.T.: The various faces of nacionalism - politics, religion, and ethos